FLUKA simulation of target fragmentation in proton therapy. (December 2020) - Embriaco, A.; Attili, A.; Bellinzona, E.V.; Dong, Y.; Grzanka, L.; Mattei, I.; Muraro, S.; Scifoni, E.; Tommasino, F.; Valle, S.M.; Battistoni, G.
Highlights: MC calculation of dose average LET and RBE evaluation. Cross Sections for the production of secondary particles in proton therapy. Calculation of fluence of secondary particles at different depth in water for the implementation in a TPS of next generation. Abstract: In proton therapy, secondary fragments are created in nuclear interactions of the beam with the target nuclei. The secondary fragments have low kinetic energies and high atomic numbers as compared to primary protons. Fragments have a high LET and deposit all their energy close to the generation point. For their characteristics, secondary fragments can alter the dose distribution and lead to an increase of RBE for the same delivered physical dose. Moreover, the radiobiological impact of target fragmentation is significant mostly in the region before the Bragg peak, where generally healthy tissues are present, and immediately after Bragg peak. Considering the high biological impact of those particles, especially in the case of healthy tissues or organs at risk, the inclusion of target fragmentation processes in the dose calculation of a treatment planning system can be relevant to improve the treatment accuracy and for this reason it is one of the major tasks of the MoVe IT project. In this study, Monte Carlo simulations were employed to fully characterize the mixed radiation field generated by target fragmentation in proton therapy. The dose averaged LET has been evaluated in case of a Spread Out Bragg Peak (SOBP). Starting from LET distribution, RBE has been evaluated with two different phenomenological models. In order to characterize the mixed radiation field, the production cross section has been evaluated by means of the FLUKA code. The future development of present work is to generate a MC database of fragments fluence to be included in TPS.